THE USE OF ICT IN ESL CLASSROOMS IN MANIPUR - Rosy Yumnam (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
The use of Information and Communication Technology (ICT) in education has increased manifold in the present times. The role and use of ICT as a tool for English Language Teaching (ELT) is increasingly explored by educators as they assist in creating collaborative and independent learning environment. ICT plays a pertinent role in enhancing motivation, creativity and critical thinking of the learners. In the study, the attitudes of the students and teachers of the secondary schools of Manipur, a state in northeast India towards using ICT in teaching and learning English language are investigated. The paper aims to make the teachers and learners aware of the use of ICT in English as a Second Language (ESL) classroom. Through the questionnaires administered to both teachers and learners, the importance and challenges in the pedagogy of ELT using ICT is identified and discussed. The findings of the survey indicate that most of the teachers and learners held positive approach towards integrating ICT in teaching and learning English language.